Theoretical Study of Islamic Jurisprudence (Ushul Fiqh) in the Era of Prophet - Syarif Hidayattullah, Ahmad; Said, Muhammad (PT ARRUS Intelektual Indonesia, 2024)
Since the early period of Islamic history, the behavior of Muslims in all its aspects has been regulated by Islamic laws. These rules are, in essence, religious. Therefore, in its development, several efforts are always made to be based on the Qur’an, as the final Divine revelation. These applications of which are largely exemplified and operationalized by the Sunnah of the Prophet. The science of Islamic Jurisprudence/Ushûl Fiqh discusses and investigates the circumstances of the Shar'i propositions and also investigates how these propositions demonstrate the laws relating to the actions of the legally responsible/mukallaf. Therefore, the topic discussed in Ushûl Fiqh are the postulates of Islamic legal evidences/syara' in terms of their reference to the law for the actions of mukallaf. Related to the case of the Hajj vows, which unfulfilled due to death, The Prophet Muhammad established the law through analogical reasoning/qiyas. The Prophet Muhammad reminded people who made vows to obey Allah SWT more so that they fulfill their promises by obeying Allah SWT because in a hadith, it is explained that a vow is like a debt.